Vietnamese Model of Journalism in the Age of Integration and its Effects to the Civil Society and Democracy in Vietnam - Hương, Đặng Thị Thu (VNU Journal of Science: Social Sciences and Humanities; Vol 28 No 5E, 2012)
Abstract . The Economic Renovation launched by the Vietnamese Government in 1986 - as a transformation from the model of centralised economy to a model of socialist market economy - has made vital impacts on Vietnamese journalism. In addition, it was the slogans of the Communist Party - which were “face the fact, analyse exactly the truth, speak the truth” and “criticism and self-criticism” - that inspired the journalism. Having investigated the changes in Vietnamese journalism after 1986, this paper will not only explore the new characteristics of Vietnamese journalism but more importantly, their effects to the civil society and democracy inVietnam. It should be noted that due to these new characteristics, the Vietnamese journalism currently cannot be conceptualised by the well-known Schramm’s “Communist theory of Press”, and therefore, needs a new theoretical model to investigate. Key words: Model of journalism, Vietnamese renovation, state journalism, market journalism.